Implementación de guías de uso rápido y seguro mediante código QR para equipos biomédicos y simuladores de alta y mediana fidelidad para el laboratorio de simulación clínica de la universidad Antonio Nariño. (2024)
Clinical simulation has transformed health education, consolidating itself as an educational strategy focused on recreating specific realistic situations, which facilitates the acquisition of technical and practical skills. The clinical simulation approach is based on the acceptance of errors and their continuous prevention